Exploration of agr types, virulence−associated genes, and biofilm formation ability in Staphylococcus aureus isolates from hemodialysis patients with vascular access infections - Lai, Chi-Hsiang; Wong, Min Yi; Huang, Tsung-Yu; Kao, Chih-Chen; Lin, Yu-Hui; Lu, Chu-Hsueh; Huang, Yao-Kuang (Frontiers in Cellular and Infection Microbiology, 2024)
Staphylococcus aureus is a pathogen commonly encountered in both community and hospital settings. Patients receiving hemodialysis treatment face an elevated risk of vascular access infections (VAIs) particularly Staphylococcus aureus infection. This heightened risk is attributed to the characteristics of Staphylococcus aureus, enabling it to adhere to suitable surfaces and form biofilms, thereby rendering it resistant to external interventions and complicating treatment efforts. To investigate this phenomenon, our study collected 103 Staphylococcus aureus isolates from hemodialysis patients utilizing arteriovenous grafts (AVGs), tunneled cuffed catheters (TCCs), and arteriovenous fistulas (AVFs) during November 2013 to December 2021. Our findings revealed that both MRSA and MSSA isolates exhibited strong biofilm production capabilities. Additionally, we confirmed the presence of agr types and virulence genes through PCR analysis. The majority of the collected isolates were identified as agr type I. However, agr type II isolates displayed a higher average number of virulence genes, with MRSA isolates exhibiting a variety of virulence genes. Notably, combinations of biofilm-associated genes, such as eno-clfA-clfB-fib-icaA-icaD and eno-clfA-clfB-fib-fnbB-icaA-icaD, were prevalent among Staphylococcus aureus isolates obtained from vascular access infections. These insights contribute to a better understanding of the molecular characteristics associated with Staphylococcus aureus infections in hemodialysis patients and provided more targeted and effective treatment approaches.